Near-field intensity enhancement under an aberrated focusing - Sarita; Jha R.; Singh R.K. (My University, 2025)
Near-field intensity enhancement due to the plasmonic response of nanoparticles is investigated with the Mie theory and multipole expansion for an aberrated focusing system. Spherical aberration and defocusing are considered as an aberration in the focusing system. © 2023 JSAP-Optica Joint Symposia in Proceedings JSAP-Optica Joint Symposia 2023 Abstracts, JSAP 2023. All rights reserved.